Hukum Waris Islam (Telaah Pemikiran Muhammad Syahrur) - Laili, Afrohatul (Universitas Nahdlatul Ulama Blitar, 2023)
One of the figures who contributed to criticism of inheritance law was Muhammad Syahrur (Syahrur). There is no doubt about Syahrur's controversy and influence in the Muslim world. He is a contemporary scholar who tries to re-read Islamic law and reconstruct it with contemporary readings, which often results in different results from those of the fuqaha in general. Syahrur made Syahrur's main contribution in the field of Ushul Fiqh, bringing major implications to various readings and conclusions of Islamic law including inheritance law which is different from the views of previous jurists. Apart from criticizing the jurists who placed the rules of wills under inheritance, Syahrur also dismantled the